Conflict and International Relations: The Impact of Terrorism and Extremism on the Middle Eastern International Politics Agenda - Marsili, M. (Beyond the West: Politics of the Global South, 2021)
Presentation on "Conflict and International Relations: The Impact of Terrorism and Extremism on the Middle Eastern International Politics Agenda" as invited speaker in the Middle East session at the congress "Beyond the West: Politics of the Global South" organized by the Political Science and International Relations Studies Association (NECPRI) of NOVA School of Social Sciences and Humanities (NOVA FCSH).